A framework for advanced social media exploitation in government for crowdsourcing. Issue 4 (14th October 2014) - Spiliotopoulou, Lefkothea; Charalabidis, Yannis; N. Loukis, Euripidis; Diamantopoulou, Vasiliki
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to develop and evaluate, in "real-life" pilot applications, a framework for advanced social media exploitation by government agencies in their policy-making processes to promote public participation and conduct crowdsourcing. Design/methodology/approach – This framework has been developed through cooperation with public sector employees experienced in public policy-making, using both qualitative and quantitative techniques: semi-structured focus group discussions, scenarios development and questionnaire surveys. The evaluation of the framework has been conducted through semi-structured focus group discussions with public sector employees involved in the pilot applications. Findings – A framework has been developed for advanced social media exploitation by government agencies, which is based on the automated posting of policy-related content to multiple social media, and then retrieval and processing of citizens' interactions with it (e.g. views, likes, comments and retweets), using the application programming interfaces (API) of these social media. Furthermore, a supporting information and communication technologies (ICT) infrastructure and an application process model for it were developed. Its evaluation, based on "real-life" pilot applications, leads to useful insights concerning its capabilities, strengths and weaknesses. Research limitations/implications – The proposed framework has been evaluated in a small number of pilot applications, so further evaluation of it is required, in various types of government agencies and for different kinds of policy consultations. Practical/Implications – The above framework enables government agencies to communicate with wider and more heterogeneous audiences in a short time and at a low cost, increase public participation in their policy-making processes, collect useful knowledge, ideas and opinions from citizens and, finally, design better, more socially rooted, balanced and realistic policies. Originality/value – This research contributes to the development of knowledge concerning advanced practices for effective social media exploitation in government (which is currently limited, despite the considerable relevant knowledge developed in this area for the private sector), by developing and evaluating a framework for advanced and highly automated exploitation of multiple social media by government agencies. Furthermore, an evaluation methodology for such practices has been developed, which is based on sound theoretical foundations.